Basic Training on Using Sketch-Up & V-Ray Applications at SMK Negeri 6 Pekanbaru: Pelatihan Dasar Penggunaan Aplikasi Sketch-Up & V-Ray di SMK Negeri 6 Pekanbaru - Mutiara Yaumil Atika; Andrie Herdiansyah; Apriliana Hidayati Nurdin; Lusi Dwi Putri (Universitas Lancang Kuning, 2025)
The use of 3D applications in design and graphic design is one of the skills needed in the world of work in this era of globalization. So the introduction and basic training in using the 3D Sketchup and V-Ray rendering applications is expected to provide insight into science and technology-based knowledge and skills in engineering designs such as architecture, technical drawing and graphic design. Through this activity, it is hoped that vocational school students will be able to understand 3D design software, develop skills and insight, and apply the creation of design idea components into 3D form and rendering. The targets of service are students of SMK Negeri 6 Pekanbaru. The software used is Sketchup 2020 and V-Ray 2015. The execution is carried out in the form of training using the lecture method and demonstration of application use together with vocational school students participating in the training. The demo is carried out by practicing directly using a computer. At the beginning and end of this training activity, a survey and evaluation will be carried out to determine the level of absorption of the material. To carry out sustainability activities, ongoing assistance can be provided by providing training materials.